1997
DOI: 10.1093/oxfordjournals.eurheartj.a015269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of chronic heart failure patients with an augmented peripheral chemoreflex

Abstract: An augmented peripheral chemoreflex is a common finding in chronic heart failure patients, one associated with increasing severity and with the exercise hyperpnoea seen in the condition. That there was an excess of patients with non-sustained ventricular tachycardia in the group with an augmented peripheral chemoreflex may be related to the chemoreflex-driven sympathetic stimulation. The peripheral chemoreflex may be important in the pathophysiology of chronic heart failure, both in terms of symptoms and exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
105
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 29 publications
5
105
0
2
Order By: Relevance
“…3,4 Augmented peripheral chemoreceptor sensitivity in HF has also been described, which may also underlie the augmented central sympathetic outflow. 5,6 In healthy humans, hypoxia leads to increased blood flow directed to skeletal muscle, and this vasodilatation is mediated by NO release. 7 In a recent study, we reported that, paradoxically, the peripheral chemoreceptor stimulation resulted in skeletal muscle vasoconstriction in HF patients.…”
mentioning
confidence: 99%
“…3,4 Augmented peripheral chemoreceptor sensitivity in HF has also been described, which may also underlie the augmented central sympathetic outflow. 5,6 In healthy humans, hypoxia leads to increased blood flow directed to skeletal muscle, and this vasodilatation is mediated by NO release. 7 In a recent study, we reported that, paradoxically, the peripheral chemoreceptor stimulation resulted in skeletal muscle vasoconstriction in HF patients.…”
mentioning
confidence: 99%
“…By contrast, other groups ,Ponikowski & Banasiak, 2001,Ciarka et al 2006 have found an enhanced ventilatory response to hypoxia in CHF patients, particularly those in more severe stages of heart failure. In addition, heightened peripheral chemoreflex function correlates significantly with the enhanced ventilatory response to exercise and dyspnea observed in these patients (Chua et al 1997,Ciarka et al 2006). …”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 91%
“…6 -9 The cause of the heightened sympathetic drive is not known. Possible mechanisms include impaired inhibitory cardiac and arterial baroreflex function, 9,10 abnormalities in central neural control, 1 and augmented sympathetic excitatory chemoreceptor [11][12][13][14][15] and somatic reflexes. 1,16 The role of chemoreflex mechanisms in heart failure has recently received considerable attention.…”
mentioning
confidence: 99%
“…1,16 The role of chemoreflex mechanisms in heart failure has recently received considerable attention. [11][12][13][14]17,18 Chemoreflexes are the dominant control mechanisms regulating ventilatory responses to changes in arterial oxygen and CO 2 content. 19 -22 The peripheral chemoreceptors, located in the carotid bodies, respond primarily to hypoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation